Radiological Evaluation of Penetration of the Irrigant according to Three Endodontic Irrigation Techniques - Said Dhaimy; Sara Imdary; Sara Dhoum; Imane Benkiran; Amal El Ouazzani (International Journal of Dentistry)
Introduction. This experimental study is to compare radiographs based on the penetration depth of the irrigant following three final irrigation techniques. Material and Method. A sample of sixty teeth with single roots were prepared with stainless steel K files followed by mechanized Ni-Ti files iRace® under irrigation with 2.5% sodium hypochlorite. Radiopaque solution was utilized to measure the penetration depth of the irrigant. Three irrigation techniques were performed during this study: (i) passive irrigation, (ii) manually activated irrigation, and (iii) passive irrigation with an endodontic needle CANAL CLEAN®. Radiographs were performed to measure the length of irrigant penetration in each technique. Results. In comparison, passive irrigation with a conventional syringe showed infiltration of the irrigant by an average of 0.682±0.105, whereas the manually activated irrigation technique indicated an average of 0.876±0.066 infiltration. Irrigation with an endodontic syringe showed an average infiltration of 0.910±0.043. The results revealed highly significant difference between the three irrigation techniques (α=5%). Conclusion. Adding manual activation to the irrigant improved the result by 20%. This study indicates that passive irrigation with an endodontic needle has proved to be the most effective irrigation technique of the canal system.